Rabindranath Tagore’s সমাজ/samaj/communities of song - McDonald, PD (ICI Berlin Press, 2024)
What happens when songs or lyric poems, composed at particular moments, become state anthems, performed again and again across generations? This essay addresses this question through the extraordinary figure of Rabindranath Tagore, who, despite his radically anti-statist vision of community, composed songs that became the celebrated national anthems of India and Bangladesh.